پەیوەندی ڕەوشی کۆمەلایەتی و ئابوری خێزان بە وەچەخستنەوە توێژینەوەیەکی سۆسیۆلۆجی یە لە هەرێمی کوردستان - محمد, کەژاڵ حسین; حمە, نەخشین بکر (Sulaimani Journal for Humanities, 2022)
Reproduction is one the most important and the controversial topic that is discussed both at the national and the international level. The reason is that the development of the socio- economic systems in all countries and the quality of the life in a society and well as in a single family has been affected by the rate of the reproduction of the world’s population. This made the author to be interested in the studying of this popular topic. The study is based on several national and international literature resources as well as analytic data using descriptive statistics. The research was performed nationally, and thus it focused on Kurdish society. The result of this study, which is presented in a master thesis, showed that there are several factors which are effect on reproduction rate and fertility among the population in the country. In addition to the socio-economic development in the country, the cultural and religious perspectives on contraception are the most important influences on the reproduction and family planning in the Kurdish society. To provide a more accurate conclusion, a variety of studies using larger population are needed.